Mechanisms of regeneration - Galliot, Brigitte (Current topics in developmental biology, 2014)
This new volume of Current Topics in Developmental Biology covers the area of mechanisms in regeneration. With an international board of authors, it provides a comprehensive set of reviews covering such topics as control of growth during regeneration, skeletal muscle degeneration and regeneration in mammals and flies, and suppression of regeneration in mammals. Covers the area of mechanisms in regeneration International board of authors Provides a comprehensive set of reviews